NORMATIVE ANTHROPOLOGY AFTER GAUDIUM ET SPES: INSIGHT FOR A LIBERATIVE ETHIC - Jechura, Chet Mitchell (Asian Horizons, 2013)
The Second Vatican Council (1962-1965) signalled a significant shift in the trajectory of the Roman Catholic Church. The spirit of aggiornamento, which effectively opened the doors of the Church to the world, had a notable impact on the way in which we think about the human person as a moral agent. The human person as a moral agent is an embodied person who lives in relationship with God and with creation, including other human beings and all living organisms on the earth. Sustained reflection on how we live in relationship to each other, to God, and to our planet lies at the heart of theological ethics. However, we know that fractures abound in these relationships, sweeping far too many persons to the margins. As a result, theological ethics must always begin from the recesses of the dominant purview. In this essay, I celebrate Gaudium et Spes as a point of departure and use theological anthropology and reflection on the body as two additional resources that can generate a robust liberative ethic, which has the capacity to raise our collective consciousness to hear the voices of those who inhabit the margins.